Optimization of the production of organic cherry tomatoes through an innovative bioinoculation technology - Iparraguirre, Julia; Masciarelli, Oscar; López, Vanesa; Mulko, José; Piatti, Daniela; Llanes, Analía (Ediciones INTA, 2025)
Biological products are sustainable alternatives to reduce the overuse of chemical fertilizers in agriculture. However, little is known about the effects of such products on cherry tomatoes. This study evaluated the performance of Azospirillum argentinense Az39 (AZ) and an extract of Macrocystis pyrifera (AE) on this variety of tomato. The products were assayed on their own and in combination, and two methods of application were tested: seed inoculation and seedling immersion. The treatments were assessed in terms of their efficacy in promoting crop growth and flowering. The combination of AE and AZ led to an increase in germination (10%), the fresh and dry weight (74% and 80%) of plants, and the chlorophyll content (50%) in the leaves of cherry tomato compared with the controls (application method with distilled water). In addition, the plants treated with AE+AZ had a larger number of floral petioles and flowers (300%) than the controls. No significant differences were found between inoculation and immersion, and a small volume of solution was enough for inoculation to be successful, i.e., for bacteria to effectively colonize the seeds. These findings demonstrate that seed inoculation with AE+AZ is a promising biotechnological tool to improve the production of cherry tomatoes.